Q) If in Δ ABC, AD is median and AE ⊥ BC, then prove that AB2 + AC2 = 2 AD2 + \frac{1}{2} BC2

Ans: 

Step 1: Let’s make a diagram for the question:

If in Δ ABC, AD is median and AE ⊥ BC, then prove that AB2 + AC2= 2 AD2 +1/2 BC2

Step 2: In Δ ABE, ∠ AEB is 900

∴ by Pythagoras theorem: AB2 = AE2 + BE2    …….. (i) 

Similarly, In Δ ACE, ∠ AEC is 900,

∴ by Pythagoras theorem: AC2 = AE2 + CE2 ……… (ii) 

Step 3: By adding equations (i) and (ii), we get:

AB2 + AC2 = (AE2 + BE2 ) + (AE2 + CE2)

∴ AB2 + AC2 = 2 AE2 + BE2 + CE2 ………….(iii)

Step 4: In Δ ADE, ∠ AED is 900

∴ by Pythagoras theorem: AD2 = AE2 + DE2   

∴ AE2 = AD2 – DE2    …….. (iv) 

Since BE = BD + DE

∴ BE2 = (BD + DE)2    = BD2 + DE2  + 2 BD . DE …….. (v)

Similarly, since CE = CD – DE

∴ CE2 = (CD – DE)2    = CD2 + DE2  – 2 CD . DE …….. (vi)

Step 5: By substituting values from equations (iv), (v) and (vi) into equation (iii), we get:

∴ AB2 + AC2 = 2 AE2 + BE2 + CE

= 2 (AD2 – DE2 ) + (BD2 + DE2  + 2 BD . DE) + (CD2 + DE2  – 2 CD . DE)

= 2 AD2 \cancel{2 DE^2} + BD2 + \cancel{DE^2} + 2 BD . DE + CD2 + \cancel{DE^2} – 2CD . DE

∴ AB2 + AC2 = 2 AD+ BD2 + 2 BD . DE + CD2 – 2 CD . DE ……………. (vii)

Step 6: Since D is the mid-point of BC, hence, BD = CD

∴ AB2 + AC2 = 2 AD+ BD2 + 2 BD . DE + (BD)2 – 2 (BD) . DE

= 2 AD+ BD2 + \cancel{2 BD . DE} + BD2\cancel{2 BD . DE}

∴ AB2 + AC2 = 2 AD+ 2 BD2 …………….. (viii)

Step 7: Since D is the mid-point of BC, hence, BC = 2 BD

∴ BD = \frac{BC}{2}

∴ AB2 + AC2 = 2 AD+ 2 (\frac{BC}{2})^2

∴ AB2 + AC2 = 2 AD+ \frac{1}{2} BC2

Please press the “like” button if you like the solution. 

Leave a Comment

Your email address will not be published. Required fields are marked *

Scroll to Top